Bond strength of self-adhesive resin cements to tooth structure - Susan Hattar; Muhanad M. Hatamleh; Faleh Sawair; Mohammad Al-Rabab'ah (Elsevier, 2015)
Objectives: The aim of this study was to evaluate the strength of the bond between newly introduced self-adhesive resin cements and tooth structures (i.e., enamel and dentin). Methods: Three self-adhesive cements (SmartCem2, RelyX Unicem, seT SDI) were tested. Cylindrical-shaped cement specimens (diameter, 3 mm; height, 3 mm) were bonded to enamel and dentin. Test specimens were incubated at 37 °C for 24 h. The shear bond strength (SBS) was tested in a Zwick Roll testing machine. Results were analyzed by one-way ANOVA and t-test. Statistically significant differences were defined at the α = 0.05 level. Bond failures were categorized as adhesive, cohesive, or mixed. Results: The SBS values ranged from 3.76 to 6.81 MPa for cements bonded to enamel and from 4.48 to 5.94 MPa for cements bonded to dentin (p > 0.05 between surfaces). There were no statistically significant differences between the SBS values to enamel versus dentin for any given cement type. All cements exhibited adhesive failure at the resin/tooth interface. Conclusions: Regardless of their clinical simplicity, the self-adhesive resin cements examined in this study exhibit limited bond performance to tooth structures; therefore, these cements must be used with caution. Keywords: Self-adhesive, Shear bond strength, Enamel, Dentin, Cement